Emergence of quinolone-resistant Shigella flexneri in Italy (March 2017). (October 2018) - Zatta, Marta; Di Bella, Stefano; Busetti, Marina; Michelacci, Valeria; Owczarek, Slawomir; Luzzi, Ida; Luzzati, Roberto
In March 2017, a 45-year-old Italian man who has sex with men was admitted to the Infectious Diseases Department of Trieste Hospital (northeast Italy), because of fever, abdominal pain and dysentery. The patient had neither foreign travel history nor sexual contact with non-Italian partners. Stool cultures grew multidrug-resistant Shigella flexneri (resistant to ampicillin, chloramphenicol, streptomycin, tetracycline, trimethoprim, amoxicillin/clavulanic acid and ciprofloxacin) and whole genome sequencing detailed the resistance features. The phylogenetic analysis showed that the strain was unrelated to any previously reported strain. The patient was treated successfully with ceftriaxone. We hereby report the first case of locally-acquired, multidrug-resistant S. flexneri infection in Italy and also the emergence of a new clone.